Analisis Ayat-Ayat Sosial Dalam Al-Qur’an Menggunakan Pendekatan Sejarah - Bela Adil Pertiwi; Kusnadi Kusnadi; Pathur Rahman (Penerbit Hellow Pustaka, 2026)
This study aims to analyze the social verses in the Qur’an using a historical approach in order to understand the social values contained therein and their relevance to contemporary social life. This study employs a qualitative method, specifically library research, by examining various sources related to Qur’anic exegesis, social verses, and the historical approach in exegetical studies. Data were collected through documentation techniques from primary and secondary sources, including the Qur’an, exegetical works, scientific journals, and relevant academic literature. Data analysis was conducted using a descriptive-analytical approach by examining the socio-historical context of the revelation of the verses (asbab al-nuzul) and interpreting the social meaning of the verses contextually. The research findings indicate that the social verses in the Qur’an contain fundamental principles regarding human equality, justice, social solidarity, and concern for vulnerable social groups. The historical approach helps uncover the social context behind the revelation of the verses, enabling the verses’ messages to be understood more comprehensively and applied effectively in modern society. This study concludes that the social teachings in the Qur’an have strong relevance as ethical and moral guidelines for building a just, harmonious, and civilized society.